Motion planning algorithms for stratified kinematic systems with application to the hexapod robot - Harmati, István; Kiss, Bálint (Acta Cybernetica, 2001)
The paper addresses the motion planning problem of legged robots. Kinematic models of these robots are stratified, i.e. the equations of motion differ on different strata. An improved version of the motion planning algorithm proposed in the literature is compared with two alternative solutions via the example of the six-legged (hexapod) robot. The first alternative solution uses explicit integration of the vector fields while the second one exploits the flatness of a restricted subsystem.